Consumer Clothing Carbon Footprint Accounting and Evaluation (Journal of Fiber Bioengineering and Informatics, 2024)
Sustainability in the fashion and textile industry is becoming a significant research focus due to globalwarming and climate change. However, more research is needed on consumers’ carbon emissions inthe context of clothing consumers. This study focuses on consumers and develops a comprehensiveaccounting model of the carbon footprint of clothing consumption. A simulation experiment is conductedthrough surveys and empirical data to calculate the carbon emissions associated with consumers engagingin clothing purchase and clothing use. The sensitivity analysis examines the factors influencing carbonemissions at each stage. The finding reveals that in the overall carbon footprint of clothing consumers,clothing use has the highest impact than clothing purchase. The findings from this study offer valuableinsights for consumers looking to reduce their carbon footprint during clothing purchase and use andalso serve as a foundation for future research endeavours, which has great significance for the reductionof carbon emissions in society as a whole.
Keywords: Clothing Consumption; Consumer Behavior; Carbon Footprint; Sensitivity Analysis.